G202(P) Management and presentation of coeliacdisease in a district general hospital. (24th May 2017) - Gadde, M; Babu, S
Abstract : Background: Coeliac Disease (CD) is an immune-mediated enteropathy caused by a permanent sensitivity to gluten in genetically susceptible individual. Recent NICE guidelines sets out the guidance for the diagnosis and management of CD. It recommends that all patients should be seen by a specialist, require dietician input and be annually reviewed. Children from the entire the county of Lincolnshire are referred to Lincoln County Hospital (LCH) for their diagnosis and are managed by a single consultant paediatrician with an interest in gastroenterology. Aims: 1) To compare our practice for the diagnosis and management of children with coeliac disease over a 5 year period from 2009 to 2014 with the current NICE guidelines. 2) To look at any change in presentation/practice from the previous audit.(1999–2004) Methods: Retrospective review of the patients diagnosed with coeliac disease over a 5 year period from 2009–2014 in LCH was undertaken and compared with the previous audit (1999– 2005). Age of presentation, duration of symptoms, clinical presentation, serology, biopsy findings, management, follow-up and sibling screening data were collected and compared.Excluded diagnosed elsewhere. Results: 65 children (23M, 42F) were diagnosed with CD in 2009–2014 vs 41 (19M, 22F) in previous audit. Mean age of diagnosis 8.1 yr vs 6.1 years, Duration of symptoms was same in both 6–8months, 65% presented with gastrointestinal symptoms vs 49%, Associated disorder 5% vs 7%, Asymptomatic 7% vs nil, Latent celiac 8% vs 12%, EMA and TtG 100% vs 100% and 7% in previous audit, HLA typing 4% vs 14%, Biopsy done in 97% in both audit, Dietician reviewed 100% in both audit, Sibling screened 55% vs 100%, Follow up in Coeliac clinic 83% vs 87%, First Degree relative 21% vs 14% in previous audit. Associated conditions see included type-IDDM, Down's syndrome, Addison's disease, Skeletal dysplasia. Conclusion: We noted that there was a significant increase in the number of patients with CD and that they presented at a slightly older age. More patients had gastrointestinal symptoms.Only 5% less than3rd centile. 7% were asymptomatic. The incidence of CD in first degree relative was high at 21%. Our practice is compliant with the NICE guidelines and ESPHAGAN.